Gas sensing and conductivity relationship on nanoporous thin films: A CaCu3Ti4O12 case study - Felix, A. A. [UNESP]; Longo, E. [UNESP]; Varela, J. A. [UNESP]; Orlandi, M. O. [UNESP] (Elsevier, 2016)
In this work, CaCu3Ti4O12 (CCTO) thin films were synthesized with the polymeric precursor method and characterized by structural (X-ray diffraction) and morphological (scanning electron microscopy) techniques. These films were composed of a single CCTO phase and presented high surface porosity. The gas sensing response and conductivity-type relationship were investigated by two different approaches. Gas sensing measurements performed at different temperatures using different atmospheres showed that the CCTO has n-type gas sensing behavior and can detect small amounts of oxidizing gases with high sensitivity and selectivity. The type of intrinsic conductivity was also investigated through thermopower measurements, which indicated intrinsic n-type conductivity in CCTO thin films prepared with the polymeric precursor method and confirmed the direct relationship between the gas sensing behavior and the intrinsic conductivity of CCTO.
Keywords: CaCu3Ti4O12; Conductivity; Gas sensing; Thermopower measurement; Thin film